Climate change alters interannual variation of grassland aboveground productivity: evidence from a 22-year measurement series in the Inner Mongolian grassland - Ma, Wenhong; Liu, Zhongling; Wang, Zhiheng; Wei Wang; Liang, Cunzhu; Tang, Yanhong; He, Jin-Sheng; Fang, Jingyun (Journal of Plant ResearchJournal of Plant Research, 2010)
Abstract Climate change is known to influence interannual variation in grassland aboveground net primary productivity (ANPP), or seasonal biomass, but direct, long-term ground observations are rare. We present a 22-year (1982-2003) measurement series from the Inner Mongolia grassland, China, to examine the effect of climate change on interannual variations in ANPP and monthly aboveground biomass (MAB). ANPP exhibited no increase over 1982-2003 but there was an association with previous-year precipitation. MAB in May increased by 21.8% from 47.8 g m鈭? (averaged for 1982鈥?984) to 58.2 g m鈭? (2001鈥?003), whereas there was no significant variation in June, July and August, and a decrease of 29.7% in September. The MAB increase in May was correlated with increases in precipitation and temperature in the preceding months. These findings suggest that the effects of climate change on grassland production vary throughout the growing season, with warmer and wetter springs resulting in increased biomass early in the growing season, and drier falls causing a decrease in biomass late in the growing season.